Managing Risk and Facilitating Trade in the COVID-19 Pandemic - World Bank (World Bank, Washington, DC, 2020)
Maintaining trade flows as much as possible during the COVID-19 pandemic will be crucial in providing access to essential food and medical items and in limiting negative impacts on jobs and poverty. Some countries are closing border crossings and implementing protectionist measures such as restricting exports of critical medical supplies. Although these measures may in the short-term provide some immediate reduction in the spread of the disease, in the medium term they may undermine health protection, as countries lose access to essential products to fight the pandemic. Instead, governments should refrain from introducing new barriers to trade and consider removing import tariffs and other taxes at the border on critical medical equipment and products, including food, to support the health response. Trade facilitation measures can contribute to the response to the crisis by expediting the movement, release, and clearance of goods, including goods in transit. The World Bank Group provides guidance and technical assistance to developing and least developed countries to implement best practices to facilitate the free flow of goods. This note provides initial guidance on measures: to support business continuity and protection of front-line officers, and to facilitate safe cross-border trade, which includes (i) handling of relief/emergency consignments, (ii) enhanced use of risk management, safe processing of risk passengers and (iii) increased internal and external border agency collaboration.